Ambiguous Territory Design for a World Estranged. (11th January 2019) - Dwyre, Cathryn; Perry, Chris; Salomon, David; Velikov, Kathy
Abstract : Why does this issue of AD foreground hardly any examples of actual buildings? This is one of a number of challenges to its content posed byCathryn Dwyre, Chris Perry, David Salomon and Kathy Velikov, who together curated the exhibition 'Ambiguous Territory: Architecture, Landscape, and the Postnatural' that has been touring the eastern US. They look back over the history of the 'machine aesthetic' and related paradigms, and question the very notion of the Post‐Anthropocene, before going on to present work from their exhibition that explores the potential for architecture to engage with infrastructure through productive estrangement.